Analysis of changing pan evaporation in the arid region of Northwest China. Issue 4 (26th April 2013) - Li, Zhi; Chen, Yaning; Shen, Yanjun; Liu, Yongbo; Zhang, Shuhua
Key Points Ep decreased from 1958 to 1993 but increased since then Ep mostly due to changes in the aerodynamic component WS and VPD are both primary factors of the reversion of Ep